Bicarbonate Within: A Hidden Modulator of Antibiotic Susceptibility - Selvi C. Ersoy; Warren E. Rose; Richard A. Proctor (Antibiotics)
Since its standardization, clinical antimicrobial susceptibility testing (AST) has relied upon a standard medium, Mueller-Hinton Broth/Agar (MHB/A), to determine antibiotic resistance. However, this microbiologic medium bears little resemblance to the host milieu, calling into question the physiological relevance of resistance phenotypes it reveals. Recent studies investigating antimicrobial susceptibility in mammalian cell culture media, a more host-mimicking environment, demonstrate that exposure to host factors significantly alters susceptibility profiles. One such factor is bicarbonate, an abundant ion in the mammalian bloodstream/tissues. Importantly, bicarbonate sensitizes methicillin-resistant Staphylococcus aureus (MRSA) to early-generation β-lactams used for the treatment of methicillin-susceptible S. aureus (MSSA). This “NaHCO3-responsive” phenotype is widespread among US MRSA USA300/CC8 bloodstream and skin and soft tissue infection isolates. Translationally, β-lactam therapy has proven effective against NaHCO3-responsive MRSA in both ex vivo simulated endocarditis vegetation (SEV) and in vivo rabbit infective endocarditis (IE) models. Mechanistically, bicarbonate appears to influence mecA expression and PBP2a production/localization, as well as key elements for PBP2a functionality, including the PBP2a chaperone PrsA, components of functional membrane microdomains (FMMs), and wall teichoic acid (WTA) synthesis. The NaHCO3-responsive phenotype highlights the critical role of host factors in shaping antibiotic susceptibility, emphasizing the need to incorporate more physiological conditions into AST protocols.